2019
DOI: 10.1002/ajmg.c.31740
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Beckwith‐Wiedemann spectrum: Diagnosis and management

Abstract: Beckwith‐Wiedemann syndrome (BWS) is the most common epigenetic overgrowth and cancer predisposition disorder. Due to both varying molecular defects involving chromosome 11p15 and tissue mosaicism, patients can present with a variety of clinical features, leading to the newly defined Beckwith‐Wiedemann spectrum (BWSp). The BWSp can be further divided into three subsets of patients: those presenting with classic features, those presenting with isolated lateralized overgrowth (ILO) and those not fitting into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
104
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(123 citation statements)
references
References 47 publications
12
104
0
7
Order By: Relevance
“…In BWS, the frequencies of the molecular subgroups corresponded to that of previous studies (e.g. [1,21,22]), with IC2 LOM as the most frequent findings, followed by upd(11)pat. In 9.5% of cases diagnosed as upd(11)pat (4 out of 42), a mosaic paternal uniparental diploidy (also known as genome-wide uniparental disomy) could be identified.…”
Section: Discussionsupporting
confidence: 82%
“…In BWS, the frequencies of the molecular subgroups corresponded to that of previous studies (e.g. [1,21,22]), with IC2 LOM as the most frequent findings, followed by upd(11)pat. In 9.5% of cases diagnosed as upd(11)pat (4 out of 42), a mosaic paternal uniparental diploidy (also known as genome-wide uniparental disomy) could be identified.…”
Section: Discussionsupporting
confidence: 82%
“…The expression study found that the 11p15.5 region of BWS is an imprinted gene cluster, its p57 mutation, IGF2/H19 transcriptional abnormality chromosomal translocation (inversion) and methylation of CpG island upstream of LITI gene may be the cause of BWS. These genes have a tendency to share regulatory mechanisms, so the onset of BWS may be the result of multiple genes, but the exact pathogenesis remains to be further studied [16].…”
Section: Discussionmentioning
confidence: 99%
“…First-line diagnostic testing is usually performed on DNA derived from blood-leukocytes (2). Other samples such as buccal swabs, skin fibroblasts, or cells of mesenchymal origins including surgical resections and/or excisions of hyperplastic tissues, can improve the detection of mosaicism (3,35,36). A negative result does not exclude a diagnosis of BWS and may be the result of low-level mosaicism that is below the level of detection, a rare balanced chromosomal rearrangement, or another currently unrecognized cause (2).…”
Section: Overview Of Genetic Testing Strategiesmentioning
confidence: 99%
“…In up to 20% of patients with a BWS phenotype, a molecular diagnosis remains unknown (1). This may be due to tissue mosaicism, as testing multiple tissues improves diagnostic yield (3). Patients without a confirmed molecular diagnosis should be evaluated for clinical features suggestive of different diagnosis and appropriate additional testing should be considered (2).…”
Section: Overview Of Genetic Testing Strategiesmentioning
confidence: 99%
See 1 more Smart Citation